The impact of anti-phosphatidylserine/prothrombin antibodies on pregnancy outcomes in patients with unexplained recurrent implantation failure: a retrospective cohort study - Han, Donglin; Zhou, Jiansuo; Shi, Jing; Yang, Nan; Liu, Qiong; Zhang, Jun; Wang, Haiyan; Wang, Yang; Zhao, Jie (Frontiers in Immunology, 2026)
BackgroundUnexplained recurrent implantation failure (URIF) represents a complex and challenging condition in reproductive medicine, while the role of non-criteria antiphospholipid syndrome antibodies in its pathogenesis remains unclear. As a non-criteria antiphospholipid syndrome antibody, anti-phosphatidylserine/prothrombin antibodies were investigated in this study to explore their effects on oocyte quality and pregnancy outcomes in patients with unexplained recurrent implantation failure.MethodsThis was a retrospective cohort study that included 853 IVF/ICSI cycles from patients with URIF at Peking University Third Hospital between April 2021 and April 2023, with patients stratified into positive and negative groups for anti-phosphatidylserine/prothrombin antibodies. Propensity score matching (PSM) was conducted at a 1:3 ratio to adjust for potential confounding factors. The primary outcome was the cumulative live birth rate, and secondary outcomes included the live birth rate per transfer cycle, miscarriage rate, and oocyte quality.ResultsAfter PSM, no significant differences were detected between the aPS/PT-positive and negative groups in terms of the oocyte and embryo parameters. Compared with the aPS/PT-negative group, the positive group presented a lower cumulative live birth rate (20% vs 32.1%, p<0.05) and a higher miscarriage rate (41.4% vs 20.4%, p<0.05). After adjusting for confounding factors via binary logistic regression (for miscarriage) and multivariate Cox models (for cumulative live birth), the results revealed that aPS/PT antibody positivity may be a potential independent risk factor for miscarriage in patients with URIF (OR = 3.753, 95% CI: 1.297-10.854, p<0.05), but its correlation with cumulative live birth rate was not significant (HR = 0.391, 95% CI: 0.391-1.179, p=0.170).ConclusionAnti-phosphatidylserine/prothrombin antibody (aPS/PT) positivity may be a risk factor for increased miscarriage rates in patients with unexplained recurrent implantation failure.